Estruturação das comunidades de pequenos mamíferos não-voadores no bioma Caatinga: enfoque em metacomunidades, betadiversidade e filobetadiversidade - Martins, Thais Kubik (2018)
The responsible factors of the structure and the regionalization of biological communities on ecosystems can be of intrinsic (ecological and evolutive traits of species, interespecific competition) and/ or extrinsic nature (climate). There are paradigms on community ecology that relate processes such as the dispersion, the resource availability and the habitat selection (environmental filters and vicariant effects), the species interaction and the neutrality effect. It is possible measure the relative parts of these processes and to propose a set of hypotheses for the Caatinga biome and the nonvolant small mammal communities which can be investigated of the light of differing theorethical frameworks. The rainfall gradient on the Caatinga create an environmental filter on which only dry tolerant species may colonize and occupy areas with rainfall deficit. This environmental gradient between dry and mesica areas may occur due to the effects of the “brejos de altitude”. Moreover, the phytophysiognomic and geomorphological differences of the ecoregions may be determinants of the regionalization of the small mammal communities. However the interespecific competition on an unpredictable environment may benefit the generalist species and the community structure may occur of stochastic way. Finally, the geographic distance between the communities and the possible influence of species source coming from adjacent biomes may be determinants of the structure. For investigate these hypotheses, we verified the effects of the most idiosyncratic environmental variables of the biome like the temperature, rainfall and moisture variations, in addition to the effect of ecoregions, the altitudinal and the geographic distance across (1) the metacommunity structure, (2) the compositional (betadiversity) and (3) the evolutionary (phylobetadiversity) dissimilarities of the communities and (4) the degree of phylogenetic clustering of the communities. These issues are addressed on the bibliographic review, on the Chapter 1. With a database resulting of field collections, zoological collections and bibliographic references, it was possible assess these hypotheses at different spatial scales (municipality, 1° grid cell and ecoregions) and for two taxonomic levels (genus and species). The structure and the heterogeneity degree of small mammal communities were addressed through the betadiversity (Simpson and Sorensen indexes), its spatial autocorrelation and the patterns in the site-by-species matrix, on the Chapter 2. The metacommunity patterns are nested with positive boundary clumping of the limits of geographic distribution, indicating the possibility of an environmental gradient and excluding the hypothesis of the clementsian metacommunities generated by ecoregions. It was detected irreplaceable regions on the Chapada Diamantina, the Planalto do Borborema and on the edges of the biome, in addition to a high compositional dissimilarity (and evolutionary dissimilarity; Chapter 3) of the communities of the Dunas do São Francisco in relation to the other ecoregions. On the Chapter 3, it was found that the phylobetadiversity (Phylosor index) between the communities was not determined by the geographic distance and the environmental variables. However, the compositional dissimilarity (Simpson and Sorensen indexes) responded to the geographic distance, the seasonality of moisture index seasonality and annual temperature range. It was possible to observe different value ranges of these environmental variables between the small mammal communities of the north of biome, the Sertaneja Depressions and on the southern areas of Caatinga (e.g., on the Chapada Diamantina). Moreover, there is phylogenetic clustering on areas of the Chapada Diamantina and the Planalto do Borborema, in addition to the phylogenetic clustering on southern areas of the Chapada do Araripe and on the south- west “brejos de altitude” of the Planalto do Borborema. There is phylogenetic clustering and evenness occuring on the brejos de altitude, in addition to the occurrence of these two phenomena at the same grid cell (clustering, when analyzed only the brejos de altitude and evenness, when analyzed the total localities/ species of grid cell). A number of processes co-occur on the biome, with the effect of environmental variables and geographic distance determining the compositional dissimilarity, which together the nested pattern of metacommunities, it is in agree with the hypotheses of environmental filter and the limitation of the dispersion/ effect of the source of species of adjacent biomes. Regarding the degree of phylogenetic clustering / evenness, these may be according to the species competition hypothesis (phylogenetic evenness on the driest localities of the bioma). The phylogenetic clustering occurred on regions with high climatic stability, aggregating a higher number of Sigmodontinae species, a taxonomic group with low adaptation and tolerance to the dry conditions. Despite the low specialization degree of these species (i.e. the absence of a Clementsian metacommunity), there is rare and unique species (Simpson index>0), indicating the biodiversity and ecological processes that must be retained on the Caatinga.